(untitled) (Eurasian Journal of Media and Communications, 2026)
The article examines the author’s television program as a specific form of modern travel journalism. Based on theoretical approaches to the concept of the author’s program, its key features are identified: the pronounced presence of the author-host’s personality, an individual style of presenting material, subjective interpretation of facts, genre flexibility, and an orientation toward trust-based communication with the audience. Particular attention is paid to the role of the host as a meaning-forming element of the television media text. As empirical material, the article analyzes the NTV television program Poedem, Poedim